2011
DOI: 10.1021/nn202643t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graphene Films and Transistors Grown on Sapphire by Metal-Free Chemical Vapor Deposition

Abstract: We present a novel method for the direct metal-free growth of graphene on sapphire that yields high quality films comparable to that of graphene grown on SiC by sublimation. Graphene is synthesized on sapphire via the simple decomposition of methane at 1425-1600 °C. Film quality was found to be a strong function of growth temperature. The thickness, structure, interface characteristics, and electrical transport properties were characterized in order to understand the utility of this material for electronic dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
147
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 35 publications
9
147
1
Order By: Relevance
“…13), where the Al2p has been used for calibration, thus indicating the close similarities between the two systems. It is important to underline the absence of any interfacial buffer layer between Gr and alumina, which would give rise to a feature at 281.5 eV (the BE corresponding to the Al-C bonds) and 282.5 eV (Al-O-C bond) 28,29 and also to C-O bonds characteristic of epoxy, ethers, quinones and lactones, which typically show up in the C1s spectrum at binding energies4284.2 eV (ref.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…13), where the Al2p has been used for calibration, thus indicating the close similarities between the two systems. It is important to underline the absence of any interfacial buffer layer between Gr and alumina, which would give rise to a feature at 281.5 eV (the BE corresponding to the Al-C bonds) and 282.5 eV (Al-O-C bond) 28,29 and also to C-O bonds characteristic of epoxy, ethers, quinones and lactones, which typically show up in the C1s spectrum at binding energies4284.2 eV (ref.…”
Section: Resultsmentioning
confidence: 80%
“…Also the opposite approach, that is, the direct growth of graphene on top of oxide surfaces, has been tested. As an example, the CVD synthesis of graphene on sapphire 13 results in the formation of monolayer graphene with a charge carrier mobility 43,000 cm 2 V À 1 s À 1 , but requires very high temperatures (B1,800 K), which are not compatible with most of the Si CMOS processing. Zhou et al 14 , on the other hand, were able to directly grow graphene on Co 3 O 4 (111) at lower temperature using molecular beam epitaxy from a solid carbon source, but the strong interaction they observed between the graphene layer and the substrate can largely contribute to electron scattering and reduce the charge mobility.…”
mentioning
confidence: 99%
“…Furthermore, the use of THG allows a broader choice of substrates than for typical optical imaging of graphene using certain fixed-thickness oxide layers on Si(001) to facilitate optical contrast [41]. This capability to probe graphene on arbitrary substrates is an important advantage of THG over linear optical imaging since graphene has been transferred to various substrates, including silicon-on-insulator [37], sapphire [42], diamondlike carbon [43], hexagonal boron nitride [44], quartz and glass [45], and flexible polymer substrates [46][47][48][49], for photonic and electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Based four-point probe measurements, sheet resistance of the fabricated graphene was found to be about 170 -200 Ω/sq (Fig. 3 (b)), a value much lower than that of graphene directly grown on SiO 2 substrate by thermal CVD (∼2000 Ω/sq) [7][8][9]. It was revealed that the hexagonal domain graphene with relatively large domain size (> 10 µm) was directly grown on the SiO 2 substrate by our method [10].…”
mentioning
confidence: 86%
“…During this transfer, a lot of defects and impurities are introduced into graphene, which results in poor device performance. Direct growth of graphene on an insulating substrate is another approach for the fabrication of graphenebased electrical devices, and various investigations in this regard have been carried across the world [7][8][9][10]. Since the direct growth of graphene on an insulating substrate does not require any transfer process, better performance of the graphene-based device can be expected as compared with that of the graphene-based device fabricated via the transfer process.…”
mentioning
confidence: 99%